Electrical relaxation and transport properties of ZnGeP2 and 4H-SiC crystals measured with terahertz spectroscopy - Voevodin, Vladimir I.; Brudnyi, Valentin N.; Sarkisov, Yuri S.; Su, Xinyang; Sarkisov, Sergey Yu (Photonics)
Terahertz photoconductivity and charge carrier recombination dynamics at two-photon (ZnGeP2) and three-photon (4H-SiC) excitation were studied. Thermally annealed, high-energy electron-irradiated and Sc-doped ZnGeP2 crystals were tested. The terahertz charge carrier mobilities were extracted from both the differential terahertz transmission at a specified photoexcitation condition and the Drude–Smith fitting of the photoconductivity spectra. The determined terahertz charge carrier mobility values are ~453 cm2/V·s for 4H-SiC and ~37 cm2/V·s for ZnGeP2 crystals. The charge carrier lifetimes and the сontributions from various recombination mechanisms were determined at different injection levels using the model, which takes into account the influence of bulk and surface Shockley–Read–Hall (SRH) recombination, interband radiative transitions and interband and trap-assisted Auger recombination. It was found that ZnGeP2 possesses short charge carrier lifetimes (a~0.01 ps−1, b~6·10−19 cm3·ps−1 and c~7·10−40 cm6·ps−1) compared with 4H-SiC (a~0.001 ps−1, b~3·10−18 cm3·ps−1 and c~2·10−36 cm6·ps−1), i.e., τ~100 ps and τ~1 ns at the limit of relatively low injection, when the contribution from Auger and interband radiative recombination is small. The thermal annealing of as-grown ZnGeP2 crystals and the electron irradiation reduced the charge carrier lifetime, while their doping with 0.01 mass % of Sc increased the charger carrier lifetime and reduced mobility. It was found that the dark terahertz complex conductivity of the measured crystals is not fitted by the Drude–Smith model with reasonable parameters, while their terahertz photoconductivity can be fitted with acceptable accuracy.